2018
DOI: 10.1002/jor.23679
|View full text |Cite
|
Sign up to set email alerts
|

Muscle stem cell activation in a mouse model of rotator cuff injury

Abstract: Rotator cuff (RC) tears are frequently complicated by muscle atrophy. Muscle stem cells (MuSCs) repair damaged myofibers following injury, but their role in the prevention or pathogenesis of atrophy following RC tears remains undefined. We hypothesized that the RC MuSC population would be affected by supraspinatus (SS) and infraspinatus (IS) tendon transection (TT) compared to uninjured muscle in a mouse model of RC tear. C57BL6/J mice underwent unilateral SS and IS TT and contralateral sham surgery. At 3, 8, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 23 publications
3
14
0
Order By: Relevance
“…46,48 In animal models of RC injury, these cells have been found to be present as well, as identified by the marker PDGFRα/β, and were shown to expand after RC injury and co-localize to fat deposits within the muscle. 6,9,50 Inhibition of TGF-β resulted in a decrease in FI because of FAP cell apoptosis, confirming the importance of these FAP cells in FI. 7 Conditional cellular depletion of FAPs has been shown to decrease FI in animal models, further supporting the role of these cells in the development of FI.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…46,48 In animal models of RC injury, these cells have been found to be present as well, as identified by the marker PDGFRα/β, and were shown to expand after RC injury and co-localize to fat deposits within the muscle. 6,9,50 Inhibition of TGF-β resulted in a decrease in FI because of FAP cell apoptosis, confirming the importance of these FAP cells in FI. 7 Conditional cellular depletion of FAPs has been shown to decrease FI in animal models, further supporting the role of these cells in the development of FI.…”
Section: Discussionmentioning
confidence: 71%
“…32 It has recently been determined that this cell line expands after RC injury, that it co-localizes to fat deposits within the muscle, and that outcomes of RC injury and repair are dependent on FAP presence in a small-animal model. 6,50 Despite the correlation of FAPs with the development of FI, it does not suggest that the presence of FAPs is entirely deleterious. Recently, FAPs have been demonstrated to possess the capacity to transition to a beige fat phenotype both within RC tissue and in other muscle injury models.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…S atellite cells are activated after a rotator cuff tear in mice, and their biological activity is thought to play an important role in pathological changes in rotator cuff disease 28 . Meyer and colleagues found that cells from patients with partial-thickness tears had reduced proliferative capacity in vitro, but no difference in fusion, when compared with cells from untorn rotator cuff muscles and full-thickness tears 29 .…”
Section: Discussionmentioning
confidence: 99%
“…A study using electron microscope exhibited that satellite cells are uniformly distributed throughout the whole muscle. 34 Davies et al 35 reported transient activation of muscle stem cell in the murine rotator cuff muscles after tendon transection. They, however, did not examine the distribution of stem cells in the muscle.…”
Section: Discussionmentioning
confidence: 99%